Penggunaan Lamtoro Tarramba Sebagai Pakan Sapi Di Desa Teluk Santong Kecamatan Plampang Sumbawa - Dilaga, Syamsul Hidayat; Suhubdy, Suhubdy; Noersidiq , Azhary; Amin, Muhamad; Yanuarianto, Oscar (Universitas Mataram, 2024)
The SAMOTA area (Saleh Bay-Moyo Island-Mount Tambora) is a tourist destination, including the world's biosphere reserve, has the potential for grazing livestock, including the assisted villages of the Partnership and Community Development Program (PKBL) in collaboration with the University of Mataram (UNRAM) with State-Owned Enterprises (SOEs) in West Nusa Tenggara Province (NTB) based on community needs supported by the research of lecturers, farmers in the village often experience difficulties in finding feed, Especially in the dry season, they never give tree leguminosa feed like lamtoro to their livestock, so they often suffer losses in the form of shrinking body weight, easily getting sick, and even dying. Therefore, the purpose of community service activities is to conduct counseling on the use of Tarramba lamtoro as cattle feed in Teluk Santong Village, Plampang District, Sumbawa Regency. The method used was lectures and discussions, as well as demonstrations of the nursery and planting of lamtoro cv tarramba in Teluk Santong Village, Plampang District, Sumbawa Regency. The results of the implementation of the activity showed that the farmers were very satisfied (87%) with the extension activity.